2021
DOI: 10.1111/jcpp.13381
|View full text |Cite
|
Sign up to set email alerts
|

A scalable computational approach to assessing response to name in toddlers with autism

Abstract: Background: This study is part of a larger research program focused on developing objective, scalable tools for digital behavioral phenotyping. We evaluated whether a digital app delivered on a smartphone or tablet using computer vision analysis (CVA) can elicit and accurately measure one of the most common early autism symptoms, namely failure to respond to a name call. Methods: During a pediatric primary care well-child visit, 910 toddlers, 17-37 months old, were administered an app on an iPhone or iPad cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…For example, the latest study of Cognoa showed a sensitivity of 0.98 and a specificity of 0.79 for ASD screening in 425 children aged 18–72 months [ 28 , 29 ]. The same pattern was observed with Autism&Beyond, which had an ASD screening sensitivity of 0.96 [ 33 ]. One possible reason for this finding could be interference and a lack of standardization of the observations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…For example, the latest study of Cognoa showed a sensitivity of 0.98 and a specificity of 0.79 for ASD screening in 425 children aged 18–72 months [ 28 , 29 ]. The same pattern was observed with Autism&Beyond, which had an ASD screening sensitivity of 0.96 [ 33 ]. One possible reason for this finding could be interference and a lack of standardization of the observations.…”
Section: Discussionsupporting
confidence: 63%
“…Autism&Beyond is even more convenient, requiring children to watch a total of approximately 2 min of short videos for facial data collection and only approximately 20 min of questionnaire completion for caregivers. Therefore, a significant amount of time is saved [ 33 ]. In addition, digital health can help address parents’ concerns about contracting COVID-19 during travel to and from clinics given the pandemic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has revealed that children with ASD responded to their names significantly less frequently than children without ASD using computer vision analysis (CVA). The CVA also exhibited that children with ASD who did orient to name call showed a longer latency before turning their head ( 25 ), which is consistent with our results. The diminished response can be explained by the theory of social motivation and social cognition in ASD.…”
Section: Discussionsupporting
confidence: 91%
“…A computer vision algorithm was used to detect the faces in each frame of the recorded video (King, 2009). Similar to (Chang et al., 2021; Perochon et al., 2021), scarce human supervision was triggered by a face‐tracking algorithm to ensure that we tracked only the participant's face. Then, we extracted 49 facial landmarks consisting of 2D‐positional coordinates (Baltrusaitis et al., 2018) (Figure 2) that were time‐synchronized with the movies.…”
Section: Methodsmentioning
confidence: 99%